Aligning Islamic Institutional School (Madrasah) and National Curricula for Eco-Islamic English Education - Hasibuan, Kalayo; Astuti, Amelia Tri; Sassylia, Dizzy; Afifah, Nurul (JELT: Journal of English Language Teaching, 2026)
This article explores the alignment between Islamic institutional school (madrasah) curricula and Indonesia’s national curriculum to promote Eco-Islamic English Education. The integration aims to harmonize faith-based and national educational objectives by embedding Islamic environmental values into English language teaching. Madrasahs, as Islamic educational institutions, often emphasize moral and spiritual formation, while the national curriculum focuses on competency-based and global education. Aligning both can create a more holistic framework that fosters linguistic competence, ecological awareness, and spiritual responsibility. This study highlights that curriculum alignment can strengthen sustainable education by encouraging students to see environmental stewardship (khalifah fil-ardh) as both a linguistic and religious practice. Ultimately, this approach prepares learners to engage with global environmental issues through an Islamic worldview using English as a medium for understanding, reflection, and action.